2022
DOI: 10.1155/2022/5774641
|View full text |Cite
|
Sign up to set email alerts
|

OGG1 in the Kidney: Beyond Base Excision Repair

Abstract: 8-Oxoguanine DNA glycosylase (OGG1) is a repair protein for 8-oxoguanine (8-oxoG) in eukaryotic atopic DNA. Through the initial base excision repair (BER) pathway, 8-oxoG is recognized and excised, and subsequently, other proteins are recruited to complete the repair. OGG1 is primarily located in the cytoplasm and can enter the nucleus and mitochondria to repair damaged DNA or to exert epigenetic regulation of gene transcription. OGG1 is involved in a wide range of physiological processes, such as DNA repair, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 21 publications
(1 citation statement)
references
References 135 publications
0
1
0
Order By: Relevance
“…Previous research in our lab and by others has shown that B[a]P-induced oxidative DNA damage and ROS formation may lead to DNA strand breaks in nontumorigenic breast epithelial cells and human breast cancer cells [12,40,86]. In Nkrumah-Elie et al [9], the DATS-mediated attenuation of cellular carcinogenesis was shown in B BER is a major genome maintenance pathway that uses OGG1 to recognize and remove 8-oxo-7,8-dihydroguanine (8-oxoG) from oxidative DNA damage to prevent genomic instability [87]. DNA polymerase β (POLβ) is recruited to fill the single gap caused by the DNA glycosylase-initiated removal of 8-oxo-G with guanine to repair lesion damage from ROS and alkylating agents [88,89].…”
Section: Discussionmentioning
confidence: 99%
“…Previous research in our lab and by others has shown that B[a]P-induced oxidative DNA damage and ROS formation may lead to DNA strand breaks in nontumorigenic breast epithelial cells and human breast cancer cells [12,40,86]. In Nkrumah-Elie et al [9], the DATS-mediated attenuation of cellular carcinogenesis was shown in B BER is a major genome maintenance pathway that uses OGG1 to recognize and remove 8-oxo-7,8-dihydroguanine (8-oxoG) from oxidative DNA damage to prevent genomic instability [87]. DNA polymerase β (POLβ) is recruited to fill the single gap caused by the DNA glycosylase-initiated removal of 8-oxo-G with guanine to repair lesion damage from ROS and alkylating agents [88,89].…”
Section: Discussionmentioning
confidence: 99%